Waterloo : June 18, 1815: the battle for modern Europe - Roberts, Andrew, 1963-; Foreman, Amanda (New York : HarperCollins, 2005)
The epic career of Napoleon was brought to a shattering end on the evening of June 18, 1815, when his hastily formed legions faced the Anglo-Allied armies under the command of the Duke of Wellington. It was the only time these men -- the two greatest captains of their age -- fought against each other. Waterloo, once it was over, put an end to twenty-two years of French Revolutionary and Napoleonic Wars, and led to a century of relative peace and progress in Europe. When the wars of the future did come, they were fought with infinitely more appalling methods by a constantly changing balance of powers. At Waterloo, the honor of bold, lavish uniforms and, at least initially, the aesthetic beauty of battle were still intact. With precision and elegance, Andrew Roberts lucidly sets the political, strategic, and historical scene before offering a breathtaking account of each successive stage of the battle. He also draws on a recently discovered document from 1854 that casts new light on just how the battle was lost. It is a confession from a French officer that helps to explain why the French cavalry charged when it did -- unsupported by infantry or artillery,and headlong at well-defended British squares. It shows that accident rather than design may have led to the debacle that lost Napoleon the battle, the campaign, and the war. Authoritative and engrossing,Waterloo is a brilliant portrait of a legendary turning point in modern history, after which the balance of world power, the legend of Napoleon, and the art of war were never the same. An exploration of the conflict that ended the reign of Napoleon draws on new evidence about how the battle was lost,offering extensive background information about the political, strategic, and historical factors of the time while sharing new insights into the tactics employed by the French cavalry.
The campaign -- The battle -- Maps -- The Waterloo campaign -- The Battle of Waterloo -- 1. The first phase -- 2. The second phase -- 3. The third phase -- 4. The fourth phase -- 5. The fifth phase -- Conclusion -- Major Robert Dick's letter from Brussels -- Captain Fortune Brack's letter of 1835 -- The Duke of Wellington's Waterloo despatch.
Includes bibliographical references (p. 135-137) and index.
Keywords: Waterloo, Battle of, Waterloo, Belgium, 1815.; Napoleonic Wars, 1800-1815 -- Campaigns -- Belgium; Europe -- History, Military -- 19th century; France -- History -- 1789-1815.